Frequency of MRI changes suggestive of axial spondyloarthritis in the axial skeleton in a large population-based cohort of individuals aged <45 years. Issue 2 (19th November 2019) - Baraliakos, Xenofon; Richter, Adrian; Feldmann, Daniel; Ott, Anne; Buelow, Robin; Schmidt, Carsten O; Braun, Juergen
Abstract : Objective: To investigate the frequency of bone marrow oedema (BME) and fatty lesions (FL) suggestive of axial spondyloarthritis (axSpA) on MRI of the spine and sacroiliac joints (SIJ) in a general population sample. Methods: As part of a community-based cohort project (Study of Health in Pomerania), volunteers underwent spinal (sagittal T1/T2) and SIJ (semicoronal short tau inversion recovery) MRI examinations. Two calibrated readers evaluated the images to detect BME in SIJ and vertebral corners (VC) and FL in VC suggestive of axSpA using Assessment of SpondyloArthritis international Society definitions. Results: MRIs of 793 volunteers (49.4% males, mean age 37.3±6.3 years, 8.4% human leucocyte antigen-B27+) aged <45 years were evaluated. SIJ BME was seen in 136 (17.2%), VC BME in 218 (27.5%) and FL in 645 (81.4%) volunteers. SIJ BME in ≥1, ≥3 and ≥5 SIJ quadrants was seen in 136 (17.2%), 7 (0.9%) and 1 (0.1%) volunteers, respectively. In VC, BME≥1, ≥3 and ≥5 lesions were seen in 218 (27.5%), 38 (4.8%) and 6 (0.8%) volunteers, respectively, while FL≥1, ≥3 and ≥5 were seen in 645 (81.3%), 351 (44.3%) and 185 (23.3%) volunteers, respectively. Logistic regression analysis showed that BME and FL in VC were related to increasing age: OR 1.33, 95% CI 1.02 to 1.72, and OR 1.73, 95% CI 1.32 to 2.27, per decade increase, respectively. Conclusions: In this large population-based study, a high frequency of inflammatory and fatty MRI lesions suggestive of axSpA was found, especially in the spine. This indicates a limited value of such MRI findings for diagnosis and classification of axSpA. The increasing frequency with age suggests that mechanical factors could play a role.